Spatial and Temporal Variation of Zooplankton Composition Near Whale Shark Sightings in Probolinggo of East Java, Indonesia (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Whale shark occurrence in Probolinggo differs from other Indonesian locales, suggesting a link to zooplankton availability. Zooplankton composition and whale shark emergence are the focus of this study. From December 2017 to November 2018, six observation points were made each month. A plankton net filters and lugol preserves water. Olympus CX23 microscope observations were repeated twice. The spatial analysis revealed varying whale shark numbers at each station (Chi-square test, X2 = 1418.6, P